Design and implementation of power line communication using microcontroller - Naddi, Nagaraju; Subrahmanyam, Ch. (International Journal of Engineering and Technology, 2018)
Abstract – This paper proposes a novel power line communication system utilizing minimum cables. Conventionally, more number of cables is used to transmit data and power. This leads to increasing the cost, complexity in design and connections, maintenance issues and high man power. In order to avoid these drawbacks, the power line communications system is proposed to transmit the data through the existing power line cables by impressing a modulated carrier signal. The proposed power line communication system is divided into two blocks in design say Transmitter design and Receiver design. At the transmitter side, the data is encoded by using Manchester encoding scheme preceded by Frequency shift keying modulation.Similarly, at the receiver side, the process of demodulation and decoding are used for the retrieval of the original data. In this paper, the STM8 Microcontroller is utilized for the real time validation of the proposed power line communication system design.